Pembelajaran Bahasa Arab Berbasis Contextual Teaching and Learning Melalui Kitab Ta’lim Muta’alim Di Pondok Pesantren Api Al Masykur Kab. Semarang - Masud, Muhammad (MADINAH, 2019)
Learning must refer to what students must do as recipients of the lesson, because learning does not only memorize and remember, because learning is a process that is marked by a change in a person. That is, that students are able to absorb subject matter if, they can grasp meaning in the lessons they receive, and they capture meaning in their assignments, when they can associate new information with the knowledge and experience they already have. Related to this, Islamic boarding school is a place of learning with efforts to change the behavior of students to a better direction, so that many people entrust some of the responsibilities in boarding schools, especially in efforts to establish noble character. This research is intended to obtain measurable data, about the Arabic Language Learning Model Based on Contextual Teaching And Learning Through the Book of Ta'lim Muta'alim in Islamic Boarding School of API Al Masykur Kab. Semarang. The analytical method used is qualitative data analysis carried out in conjunction with the data collection process. The analysis technique was carried out using data analysis techniques which included three concurrent activities: data reduction, data presentation and conclusion drawing (verification). The results showed that: 1) Conceptualizing the learning process of the book Ta'lim al-Muta‘allim at the research location was carried out by examining the basic things that became the foundation of learning. 2) Carry out the Concept of Learning Activity Book Ta'lim al-Muta‘allim. In the research location, the concept of learning that has been compiled is carried out using the principle of interactive communication.